SELL AND BUY TRANSFER OF MOTORCYCLE WITH ADVANTAGES OF A MUAMALAH FIQH PERSPECTIVE (Case Study In Ingin Jaya Districts Aceh Besar District) - Deddy Yusuf; Saifuddin Sa'dan; Azka Amalia Jihad (Universitas Islam Negeri Ar-Raniry, 2021)
Buying and selling over motorcycle financing with profits in the District of Ingin Jaya, namely by transacting motorbikes that are still in financing by obtaining profits and this has become a habit for the people of the Ingin Jaya community. for this reason, the sellers and buyers need to know how the practice of buying and selling over motorcycle financing with profits that are in accordance with the perspective of the sale al-ba’i and hiwalah. In this study the authors used a descriptive analysis research method based on data obtained from interviews with Yamaha Sales Executive, Second Motorbike business owner Umar Matang and buyers from the general public which included transaction procedures and understanding in the agreement to set prices until the transfer was made. The results show the agreement between the seller and the buyer is based on a sense of willingness and an element of help on the condition that the leasing company that provides financing know and approves the transfer is made. And the buyer of the transferred motorbike of the Financing negotiates the transfer price with the first owner and later the buyer of the second motorbike will continue the remaining deposit. From the perspective of the Hiwalah and al-ba'i and Al-Milk At-Tamm contracts, the transfer and sale and purchase transactions that occur are very much in accordance with the concept of Hiwalah, al-ba'i, and complete ownership requirements (Al-Milk At-Tamm) in fiqh muamalah, and also the profits obtained are considered legitimate in buying and selling because the profits are obtained from goods that have clear ownership and are known between the two so that neither party is injured. The transaction has also become a good habit for the people of the District of Ingin Jaya.